The time series at the Strait of Gibraltar as a baseline for long-term assessment of vulnerability of calcifiers to ocean acidification - Amaya-Vías, Silvia; Flecha, Susana; Pérez, Fiz F.; Navarro, Gabriel; García-Lafuente, Jesús; Makaoui, Ahmed; Huertas, I. Emma (Frontiers in Marine Science, 2023)
The assessment of the saturation state (Ω) for calcium carbonate minerals (aragonite and calcite) in the ocean is important to determine if calcifying organisms have favourable or unfavourable conditions to synthesize their carbonated structures. This work examines temporal trends of ΩAragonite and ΩCalcite in three water masses that exchange in the Strait of Gibraltar: North Atlantic Central Water (NACW), Levantine Intermediate Water (LIW) and Western Mediterranean Deep Water (WMDW) using accurate measurements of carbonate system parameters collected from 2005-2021. Our analysis shows a gradual temporal decline in Ω in all water masses, with decreasing trends being more and less pronounced in the NACW and LIW, respectively. Projected long-term changes of Ω for future increases in atmospheric CO2 under the IPCC AR6 Shared Socio-economic Pathway "fossil-fuel-rich development" (SSP5-8.5) indicate that critical conditions for calcifiers with respect to aragonite 2 This is a provisional file, not the final typeset article availability will be reached in the region at all depths before the end of the current century, with a corrosive environment (undersaturation of carbonate) expected after 2100.